Framework for the geosites selection according to the International Union of Geological Sciences (IUGS), and the European Association for the Conservation of Geological - Geomorphological heritage (ProGEO). First phase: an attempt for a country framework - ΘΕΟΔΟΣΙΟΥ - ΔΡΑΝΔΑΚΗ, Ε. (Bulletin of the Geological Society of Greece, 2018)
This contribution refers to the history of the International Union of Geological Sciences (IUGS) initiative for the inventory and compilation of the global geosites list, "The geosite project". This project that started in 1996 came as a consequence of the recent years discussion in international level, geological sites to be included in global site-based conservation and protection projects and in the world heritage list of UNESCO. The Global Geosites Working Group set up by International Union of Geological Sciences (IUGS) with the support of UNESCO in 1995, undertook the initiative for the systematic inventory of the most important sites, above all for the needs of the geological sciences research and education. The project aims also, to involve the whole geological community in geoconservation, as well as to support any national or international initiative to protect geodiversity, a recourse completely unrenewable. In Europe the whole pilot work for the geosites project is carried out by ProGEO, the European Association for the geological-geomorphological heritage conservation. ProGEO to which most of Europe's nations are represented by members, through regular international congresses, meetings, workshops, has led the way for the project, supported by its regional working groups and its national representatives (Greece belongs to the ProGEO WG1 of south-eastern Europe).